GEFT Inhibits Autophagy and Apoptosis in Rhabdomyosarcoma via Activation of the Rac1/Cdc42-mTOR Signaling Pathway - Li, Chunsen; Li, Zhenzhen; Song, Lingxie; Meng, Lian; Xu, Guixuan; Zhang, Haijun; Hu, Jianming; Li, Feng; Liu, Chunxia (Frontiers in Oncology, 2021)
Autophagy and apoptosis are dynamic processes that determine the fate of cells, and regulating these processes can treat cancer. GEFT is highly expressed in rhabdomyosarcoma (RMS), which accelerates the tumorigenicity and metastasis of RMS by activating Rac1/Cdc42 signaling, but the regulatory mechanisms of autophagy and apoptosis are unclear. In our study, we found that the RMS tissues had high Rac1, Cdc42, mTOR, and Bcl-2 expression levels and low Beclin1, LC3, and Bax expression levels compared with the normal striated muscle tissues (P < 0.05). In addition, multivariate analysis has proven that Rac1 is an independent prognostic factor (P < 0.05), and the high expression level of the Beclin1 protein was closely associated with the tumor diameter of the RMS patients (P = 0.044), whereas the high expression level of the LC3 protein was associated with the clinical stage of the RMS patients (P = 0.027). Furthermore, GEFT overexpression could inhibit autophagy and apoptosis in RMS. A Rac1/Cdc42 inhibitor was added, and the inhibition of autophagy and apoptosis decreased. Rac1 and Cdc42 could regulate mTOR to inhibit autophagy and apoptosis in RMS. Overall, these studies demonstrated that the GEFT–Rac1/Cdc42–mTOR pathway can inhibit autophagy and apoptosis in RMS and provide evidence for innovative treatments.